THE DESIGN OF THE VISUAL ASSET OF JOURNALING BOOK EXPLORE MYSELF FOR MENTAL HEALTH IN GENERATION Z - PARAMITA, ANGELICA FAYOLA AYU; Tjandrawibawa, Paulina (Universitas Ciputra, 2022)
This research chose designing the visual asset of Explore Myself journaling book for mental health which aims to invite and help the Z generation to take care and learn about mental health. From this journaling book, they are expected to know themselves and become a safe place to express their feelings. The research methods that are used are primary data through interviews with expert users and extreme users and also surveys with target audience. And secondary data from literature studies from books and journals. The results of the research proved that the visual asset of a journaling book can be designed with a fun and calm design to attract the Z generation and need to do more promotion on social media to build brand awareness. Keywords: Journaling Book, Z Generation, Mental Health, Visual Asset